Parotidectomy for the treatment of parotid sialocoele in 14 dogs. (24th December 2015) - Proot, J. L. J.; Nelissen, P.; Ladlow, J. F.; Bowlt Blacklock, K.; Kulendra, N.; de la Puerta, B.; Sheahan, D. E.
Abstract : OBJECTIVES: To describe the presentation, diagnosis, cause, complications and outcome in 14 dogs that presented with a parotid sialocoele and that were treated by complete parotidectomy. MATERIAL AND METHODS: Multi‐institutional retrospective study. RESULTS: Each dog presented with a non‐painful, fluctuant, soft tissue mass over the lateral aspect of the face in the region of the parotid salivary gland. Diagnosis was made by sialoradiography (3/14), CT (3/14), ultrasound (11/14) and MRI (2/14). The cause of the sialocoele could be determined in 8 of 14 patients and included: foreign body (2/14), sialolithiasis (1/14), neoplasia (3/14), salivary gland lipomatosis (1/14) and trauma (1/14). Treatment incurred one anaesthetic complication (regurgitation) and seven postoperative surgical complications [self‐limiting seroma formation (2/14), haemorrhage (1/14), wound dehiscence (1/14), abscessation 7 months postoperatively (1/14) and facial nerve paralysis (2/14)]. Sialocoele did not recur in any dog during a median follow‐up time of 14 months. CLINICAL SIGNIFICANCE: Parotidectomy has been considered a technically challenging procedure but can have a good success rate with long‐term resolution of the clinical symptoms. Intra‐ and postoperative complications are reasonably common.